Adipocyte integrin-linked kinase plays a key role in the development of diet-induced adipose insulin resistance in male mice - Aimée R. Bugler-Lamb; Annie Hasib; Xiong Weng; Chandani K. Hennayake; Chenshi Lin; Rory J. McCrimmon; Roland H. Stimson; Michael L.J. Ashford; David H. Wasserman; Li Kang (Elsevier, 2021)
Objective: Increased deposition of the extracellular matrix (ECM) in adipose tissue (AT) during obesity contributes to insulin resistance. The integrin receptors transmit changes in the extracellular environment causing corresponding intracellular adaptations. Integrin-linked kinase (ILK), an adaptor protein, is a central hub for intracellular signaling of integrins. This study determined the role of ILK in adipose function and insulin resistance. Methods: The pathogenic role of ILK in obesity and insulin resistance was studied in human adipose tissue and adipocyte-specific ILK-deficient mice (ILKlox/loxAdCre). ILKlox/loxAdCre mice together with wild-type littermates (ILKlox/lox) were fed a chow diet or 60% high-fat (HF) diet for 16 weeks. In vivo insulin sensitivity was determined by hyperinsulinemic-euglycemic clamps. Results: AT ILK expression was increased by HF diet feeding in mice and increased in visceral fat of morbidly obese humans. The HF-fed ILKlox/loxAdCre mice displayed reduced fat mass and improved glucose tolerance relative to the HF-fed ILKlox/lox mice. During a hyperinsulinemic-euglycemic clamp, the HF-fed ILKlox/loxAdCre mice exhibited partially improved insulin resistance in AT. Lipolysis was suppressed to a greater extent by insulin and glucose uptake in brown AT (BAT) increased. Increased inhibition of lipolysis may have been attributed to increased vascularization in white AT, while increased glucose uptake in BAT was associated with increased Akt phosphorylation and P38/JNK dephosphorylation. Notably, AT insulin sensitivity in lean mice was not affected by ILK deletion. Moreover, reduced fat mass in the HF-fed ILKlox/loxAdCre mice may have been attributed to decreased free fatty acid uptake into adipocytes via the downregulation of CD36 gene expression. Consistent with the results in the mice, knockdown and knockout of ILK in 3T3-L1 cells decreased lipid accumulation and CD36 gene expression during adipogenesis. Conclusions: These data show that adipocyte ILK is important for regulating HF diet-mediated insulin resistance in AT in a manner consistent with AT function.